The blind assassin - Atwood, Margaret Eleanor, 1939- (New York : N.A. Talese, 2000)
A story within a story in which the memoir of World War II era button heiress Iris Chase alternates with a science fiction romance about a blind killer who falls in love with a mute virgin.
Library Journal Starred.
Notable/Best Books (A.L.A.).
Wilson's Fiction.
Adult
Keywords: Sisters -- Death -- Fiction; Widows -- Fiction; Domestic fiction; Psychological fiction; Science fiction; Sisters -- Death -- Fiction; Widows -- Fiction; Domestic fiction; Psychological fiction